Chronic inflammation is a feature of Achilles tendinopathy and rupture. Issue 6 (8th November 2017) - Dakin, Stephanie Georgina; Newton, Julia; Martinez, Fernando O; Hedley, Robert; Gwilym, Stephen; Jones, Natasha; Reid, Hamish A B; Wood, Simon; Wells, Graham; Appleton, Louise; Wheway, Kim; Watkins, Bridget; et al.
Abstract : Background: Recent investigation of human tissue and cells from positional tendons such as the rotator cuff has clarified the importance of inflammation in the development and progression of tendon disease. These mechanisms remain poorly understood in disease of energy-storing tendons such as the Achilles. Using tissue biopsies from patients, we investigated if inflammation is a feature of Achilles tendinopathy and rupture. Methods: We studied Achilles tendon biopsies from symptomatic patients with either mid-portion tendinopathy or rupture for evidence of abnormal inflammatory signatures. Tendon-derived stromal cells from healthy hamstring and diseased Achilles were cultured to determine the effects of cytokine treatment on expression of inflammatory markers. Results: Tendinopathic and ruptured Achilles highly expressed CD14+ and CD68+ cells and showed a complex inflammation signature, involving NF-κB, interferon and STAT-6 activation pathways. Interferon markers IRF1 and IRF5 were highly expressed in tendinopathic samples. Achilles ruptures showed increased PTGS2 and interleukin-8 expression. Tendinopathic and ruptured Achilles tissues expressed stromal fibroblast activation markers podoplanin and CD106. Tendon cells isolated from diseased Achilles showed increased expression of pro-inflammatory and stromal fibroblast activation markers after cytokine stimulation compared with healthy hamstring tendon cells. Conclusions: Tissue and cells derived from tendinopathic and ruptured Achilles tendons show evidence of chronic (non-resolving) inflammation. The energy-storing Achilles shares common cellular and molecular inflammatory mechanisms with functionally distinct rotator cuff positional tendons. Differences seen in the profile of ruptured Achilles are likely to be attributable to a superimposed phase of acute inflammation and neo-vascularisation. Strategies that target chronic inflammation are of potential therapeutic benefit for patients with Achilles tendon disease.